Rural households in Papua New Guinea afford better diets with income from small businesses - Schmidt, Emily; Mueller, Valerie; Rosenbach, Gracie (Elsevier, 2020)
Papua New Guinea is an economic leader in the Pacific region via its extractive resources. However, these industries do not provide employment opportunities for the country’s 6.4 million (80% of total population) rural inhabitants. Rural nonfarm enterprises (NFEs) could offer an additional source of structural change, whereby benefits are capitalized by domestic rural and urban households along the value chain. In 2018, we administered a survey to over 1000 households to gauge whether households with NFEs afford better diets. We examine the factors associated with NFE ownership using a multinomial logit (MNL) framework. We then evaluate whether welfare effects differ by the sex of the NFE owner using nearest neighbor matching to address selection into NFE ownership. Results suggest households with a NFE obtain greater levels of consumption on the order of 26% for protein per person, 11% for kilocalories per person, 13% for total yearly expenditures per person, and 10% for household dietary diversity. Results point to the resounding limitations of female-owned NFEs primarily created to cope with income risk. The findings highlight the relevance of NFEs as a poverty reduction strategy and the importance of targeting when promoting in-country entrepreneurship.